2021
DOI: 10.1002/ijop.12754
|View full text |Cite
|
Sign up to set email alerts
|

Left‐behind children's social adjustment and relationship with parental coping with children's negative emotions during the COVID‐19 pandemic in China

Abstract: U sing data collected from two provinces in China through an online survey, the current study aimed to investigate left-behind children's emotional and academic adjustment during the COVID-19 pandemic in China. The participants included 1780 left-behind (960 boys) and 1500 non-left-behind (811 boys) children in elementary and junior high school with a mean age of 11.23. Self-reported questionnaires concerning children's depression, loneliness, anxiety, and academic adjustment, and parents' coping with children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…Meanwhile, the crucial family factors affecting children's mental health during the home quarantine in Western China were revealed in this study. Consistent with previous studies, high-income families [58], a lack of siblings [39], living with parents [62], mothers with middle-or high-level occupations [67], frequent parent-child communication [67], and better parent-child relationships [68] were positively related to children's mental health when using regression models. However, existing studies have failed to discuss the relative effects of these factors.…”
Section: Contributionssupporting
confidence: 88%
See 1 more Smart Citation
“…Meanwhile, the crucial family factors affecting children's mental health during the home quarantine in Western China were revealed in this study. Consistent with previous studies, high-income families [58], a lack of siblings [39], living with parents [62], mothers with middle-or high-level occupations [67], frequent parent-child communication [67], and better parent-child relationships [68] were positively related to children's mental health when using regression models. However, existing studies have failed to discuss the relative effects of these factors.…”
Section: Contributionssupporting
confidence: 88%
“…Studies of migration suggest that the psychological risk of children increases when their parents move abroad. A study of left-behind children under COVID-19 also found that depression and anxiety symptoms for left-behind children were more severe and their academic adjustment was poorer [62]. Consistent with previous studies, this paper indicated that children living with both parents during the home quarantine were in a better mental health condition, and the psychological problem of children who did not live with their parents during a public crisis was challenging in Northwest China.…”
Section: • Impact Of Family Environmentsupporting
confidence: 85%
“…The authors also studied the supportive role of psychologists in the grieving process. Wang et al (2021) examined psychological implications of the pandemic in 1780 left-behind children and 1500 non-left behind children in China during the national shutdown in the first months of 2020. Left-behind children refer to those under the age of 18 who have been left alone in their hometown and cared for by people other than their parents for over 12 months.…”
Section: This Special Issuementioning
confidence: 99%
“…Unfortunately, there is a high likelihood that these children live with elderly, uncaring, or abusive caregivers. Parents’ early-age parting of LBC causes significant psychological and mental issues [ 21 , 22 , 23 ]. Moreover, due to the intensive working hours and job engagement of migrants, they cannot visit their LBC [ 24 ], which causes these children to experience loneliness, a lack of communication, and sadness [ 21 ] due to insufficient family care and parental love.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined the psychological and mental well-being of LBCs in view of their parental absence [ 7 , 21 , 23 , 25 , 26 ]. Similarly, substantial evidence has affirmed that LBCs are at high psychological risk due to parental separation [ 7 , 23 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%